Pemahaman Guru Seni Budaya (Seni Rupa) Terhadap Kompetensi Dasar (KD) Kurikulum 2013 Pada Jenjang SMA/SMK di Kota Makassar - Pangeran Paita Yunus (Seminar Nasional LP2M UNM, 2019)
The understanding of Arts and Culture teachers on Basic Competence (KD) in the art curriculum in the 2013 curriculum is the initial key to the achievement of learning objectives in the classroom. The goal agreed in this study was to describe the understanding of the teachers of art and culture (art) towards the Basic Competence (KD) in the field of fine arts at the high school / vocational level in Makassar. This research is a survey research to describe the facts that occur in the field about art and culture teachers who teach in high school / vocational high school, related to their understanding of Basic Competence (KD) subjects in the arts and culture they discuss. 15 subjects were published. This research is a quantitative descriptive study using percentages. The data technique used consisted of a questionnaire. The results of this questionnaire will be analyzed using descriptive statistical techniques and expressed as a percentage. The results of research on the understanding of art teachers on the Basic Competencies (KD) of the 2013 curriculum at the SMA / SMK level in Makassar show that some teachers do not understand and and even really lack understanding of some basic competency formulations of the meaning of basic competencies with the meaning of concepts,  the structure, theme and aesthetic value of art.